Urban settlements’ vulnerability to flood risks in African cities: A conceptual framework - Salami, Rafiu O. (Jamba, 2017)
In the recent past, the frequency and gravity of large-scale flood disasters have increased globally, resulting in casualties, destruction of property and huge economic loss. The destructive flood disaster devastating Louisiana, USA, is a recent example. Despite the availability of advanced technological capabilities for dealing with floods in developed nations, flood disasters continue to become more rampant and disastrous. Developing countries in Africa such as Benin, Ghana, Nigeria, Senegal and Sudan have recently experienced severe flooding, leaving a considerable number of human casualties and thousands displaced. In African cities, most vulnerable urban residents usually have lesser capacity and fewer resources to recover from the shocks of disaster as a result of the failure of governments to build human security for poor African residents. Many scholars have acknowledged the lack of appropriate vulnerability assessment frameworks and policies, questioning the efficiency and effectiveness of the tested models in Africa. The ability to accurately identify, measure and evaluate the various vulnerabilities of affected people and communities is a right step towards reducing disaster risk. This article aimed at developing a framework for assessing urban settlements’ vulnerability to flood risks in Africa. The framework is currently being tested to assess various dimensions of vulnerability drivers in three urban communities in Ibadan metropolis, the third largest city in Nigeria, focusing more on flood risk perceptions and behaviour of the risk bearers. It uses participatory and mixed method approaches to socially construct vulnerability of populations at risk. This model emanates from the evaluation of considerable relevant literature and an array of vulnerability assessment frameworks. It integrates some approaches that are applicable to African cities in a bid to create a versatile tool to assess, identify and mitigate the effects of flood disaster risk and reduce urban poor’s vulnerability to natural and human-induced hazards.